Genes in development re-reading the molecular paradigm - Neumann-Held, Eva M.; Rehmann-Sutter, Christoph 1959- (Duke University Press, 2006)
Genome analysis and developmental biology: the nematode Caenorhabditis elegans as a model system / Thomas Bürglin -- Genes and form: inherency in the evolution of developmental mechanisms / Stuart A. Newman and Gerd B. Müller -- From genes as determinants to DNA as resource: historical notes on development and genetics / Sahotra Sarkar -- The origin of species: a structuralist approach / Gerry Webster and Brian C. Goodwin -- On the problem of molecular versus the organismic approach in biology / Ulrich Wolf -- Genes, development, and semiosis / Jesper Hoffmeyer -- The fearless vampire conservator: Phillip Kitcher, genetic determinism, and the informational gene / Paul E. Griffiths --
Includes bibliographical references and index
Keywords: Developmental Biology; methods; Growth and Development; genetics; DNA; genetics; Evolution; Genetic Determinism; Genetic Processes; Developmental genetics